Application of the Critical Path Method in Project Planning and Management. - Kateu, Victor (Kabale University, 2024)
Project success can be hardly achieved without planning, scheduling, and estimating its duration for completion. However, even when that is so, most of the projects in Uganda are run without proper planning, and if planning is done, it is often carried out using approaches that are not effective enough to guarantee accuracy. All projects must have a deadline for their completion, but not every project goes as scheduled. This calls for the application of scientific methods such as CPM, often very useful in project management and scheduling. This study was on the application of the Critical Path Method (CPM) in project planning and management, taking a case study of the Kabale University multipurpose building construction project at the engineering faculty in Kekubo. The analytical research design was adopted for the study as the design suits the study at hand. Secondary data on the activities, their descriptions, and predecessor as well as their duration were obtained from the construction site. A weighted digraph was drawn to represent the relationship between the activities, the weights on each arrow (edge) represented the duration of the project, and vertices (nodes) represented the various activities. The longest path algorithm was then applied to establish the duration of the project and the critical path activities. These results were the same as those obtained using the CPM which gave us all critical activities and their total slacks. The results show that if CPM is applied to the project, the project can be completed in 321 days compared to the initial duration of 185 days proposed by the client. This calls for measures to be undertaken by the contractor since the project will be delayed by 136 days following the normal schedule. We recommend that CPM should be used in a building construction company before embarking on the building, that way, crashing can be done and proper resource allocation can be done to ensure successful project completion. The construction firm should devote more resources, labor, and equipment to the critical path to avoid unnecessary delay and penalties where possible.